Explaining the Concept of Palliative Care in Patients With Stroke, Development and Validation of a Questionnaire: A Mixed-Method Study Protocol - Zakiyeh Jafaryparvar; Fatemeh Bahramnezhad; Fatemeh Hajibabaee; Mahdi Shafiee Sabet; Nahid Dehghan Nayeri (International Journal of Qualitative Methods)
Introduction: Stroke is a rapidly progressive local or pervasive neurological disorder. Stroke survivors and their families experience a heavy burden of physical and psychological symptoms that are frequently left unaddressed. They often feel unprepared to transition into the post-stroke phase and constantly seek help to manage symptoms, adapt to new strategies, and navigate medical decisions. Palliative care (PC) approach can be helpful for them. Although PC is an essential element of treatment in stroke units, the phrase “PC” is often misunderstood as equivalent to end-of-life care or the termination of treatment. As a result, there are few referrals of stroke patients to specialized palliative care services, typically happening only at the time of death. Methods and Analysis: This research is sequential mixed-method exploratory analysis. It will focus on the concept of PC, its characteristics, antecedents, and consequences for stroke survivors, in addition to the creation and psychometric evaluation of a specific PC questionnaire. It includes two phases: qualitative and quantitative phase. In qualitative phase the concept of PC in acute stroke survivors will be explored by using the hybrid concept analysis technique. It includes three stages: (a) theoretical; (b) fieldwork, and (c) analytical. In quantitative phase a PC questionnaire based on the concept explained in the qualitative phase will be developed and its psychometric properties will be evaluated. It will involve producing items, determining face validity, content validity, construct validity, and reliability. Conclusion: The findings may assist in comprehending the accurate concept of palliative care in stroke patients and result in the integration of palliative care nurses and physicians as part of the treatment team for this patient group. It may result in the design of educational packages and related educational software for patients and their families to support the care of stroke patients. Additionally, the results may lead to the establishment of essential minimum training requirements in the area of palliative care following a stroke for treatment teams.